A randomized trial of healthy weight gain in athletic individuals - Sanchez, A. D.; Reynolds, J. C.; Marinik, E. L.; Kolb, R. D.; Lozano, A. J.; Davy, B. M.; Hunter, G. R.; Larson-Meyer, D. E. (Medicine & Science in Sports & Exercise, 2024)
Abstract Many athletes desire weight gain, ideally as lean body mass (LBM), to improve athletic performance. These athletes are commonly encouraged to increase energy intake by ~500 kcal/day with emphasis on adequate protein, carbohydrate, and judicious inclusion of healthy fat-containing energy-dense foods, such as peanuts/peanut butter, along with rigorous resistance training (RT). These guidelines target gains of ~0.23 kg/week. However, little is known about the efficacy of such regimens.